Recognising Religion: Emerging Jurisprudence in South Africa - Mhango, M. (Journal for the study of religion, 2012)
This paper examines the emerging jurisprudence with respect to religion in South Africa. The paper submits that South African jurisprudence has matured and will likely shape the jurisprudential trend in Southern Africa. The paper briefl y discusses the history of the religious freedom under the apartheid government of South Africa, and argues that the laws passed during apartheid government were inclined towards Christian religious values and that to some extent this has persisted in post-apartheid jurisprudence. The paper also discusses the current judicial interpretations of the freedom of religion under the South African Constitution. In this regard, the paper examines the decisions in Prince, Pillay and Popcru, and their impact on human rights and the transformative agenda of the South African society.